HIDROLISIS ENZIMATIS DAN MICROWAVE BAMBU BETUNG (Dendrocalamus asper (Schult.f.)) SETELAH KOMBINASI PERLAKUAN PENDAHULUAN SECARA BIOLOGIS DAN MICROWAVE - Widya Fatriasari, Wasrin Syafii, Nyoman Wistara, Khaswar Syamsu, Bambang Prasetya (Department of Agroindustrial Technology, Bogor Agricultural University, 2015)
Enzymatic and acid microwave-assisted hydrolysis of a newly combined biological and microwavepretreatment was developed to evaluate the reducing sugar yield of betung bamboo fibers. In previous parallelstudy of single (biological or microwave) pretreatment, the improvement of reducing sugar yield of microwaveassistedacid hydrolysis has been reported previously. The cellulase of 10 and 20 FPU/g substrate was appliedin the enzymatic hydrolysis of pretreated biomass using a shaking incubator at 50°C and 150 rpm for 48 hours.In the microwave-assisted acid hydrolysis, 1.0% sulfuric acid concentration was used either with or without theactivated carbon aditionat microwave hydrolysisat 330 watt for 7.5-12.5 minutes. There was an improvement inreducing sugar yield of bamboo pretreated biological-microwave pretreatment after microwave assisted-acidhydrolysis compared to enzymatic hydrolysis. This hydrolysis performance improvement was greater than that ofthe single pretreatment (biological or microwave pretreatment). Bamboo pretreated by biological-microwavepretreatment (5% inoculum loading and irradiated for 5 minutes at 330 W) showed the highest reducing sugaryield after microwave hydrolysis for 12.5 minutes (16.65% per dry biomass or 18.92% per dry substrate). Asmuch as 27.21% of hollocellulose can be converted to reducing sugar or 23.84% of theoritical maximumreducing sugar yield. The benefical effect of activated carbon addition in microwave assisted acid hydrolysiswas the reduction of brown compound even though oligomer adsorption caused the decreasing of reducing sugaryield.Keywords: betung bamboo, brown compound, combination of biological and microwave pretreatment, enzymaticand acid-microwave hydrolysis, reducing sugar yield